A pilot study comparing pattern of damage sustained among instruments from different surgical units in a tertiary care centre in Nepal – reappraising the role of instrument reprocessing in retaining their value [version 1; referees: 2 approved] - Sunil Munakomi; Roshan Shah; Sangam Shrestha (F1000Research, 2018)
Background: The quality of instruments plays a pivotal role in governing safe operating room culture. The reprocessing system followed in the institution determines their durability thereby ensuring patient safety as well as minimizing health spending. Rigorous reprocessing in a centralized instrument reprocessing department by well trained staff following formulated guidelines helps to achieve the target of “safe surgery saves lives” as formulated by the World Health Organization. Methods: We sought to determine the patterns of wear and tear sustained among sets of surgical equipment from two surgical units that had been sent to the repair department within a year of their purchase. Analysis of similar changes in the joints of the instrument, as well as pattern of fractures sustained was performed. Results: All patterns of wear and tear were common in both the general surgical arm and neurosurgical counterpart, with the exception of fractures and mal-alignments. Similar study was performed examining changes in the joints. Stains were the most commonly observed change pattern in both sets of instruments. Fractures were most frequent in the working ends in both sets of instruments. Conclusion: There is an alarming incidence of wear and tear patterns in the instruments used in the surgical units, even within the first year of their use. This supports the strict implementation of reprocessing guidelines by well trained workers and their quality assessments via audit checks. The quality of the purchased instruments also plays a pivotal role.